Active force control on active suspension system - Mohd Salehuddin, Idres (2013)
Active force control system is the most effective and robust system in surpass vibration on suspension system. The objective of this project is to study the performance of AFC on car suspension system. Three type of suspension were tested and compared which is passive suspension, active suspension with PID controller and active suspension with AFC system. The quarter car model is designed. Passive suspension is a suspension system that not equipped with any controller or actuator. For the active suspension, PID controller is used. This controller design deals with selection of proportional gain, derivative gain and integral gain. This parameters ( Kp, Kd and Ki ) is tuned by using try and error method. For the active suspension with AFC scheme, incorporated with PID controller, it also important to get the optimum value of estimated mass. From the result, active suspension with AFC scheme can reduce more vibration compared to active suspension with PID controller and passive suspension. In conclusion, the AFC system is the most robust and simple system in reducing the vibration on suspension system compared to active suspension with PID controller and passive suspension.